1962
DOI: 10.1103/physrevlett.9.183
|View full text |Cite
|
Sign up to set email alerts
|

Regge Pole Model for High-Energyppandp¯pScattering

Abstract: squared distributions of the H7r and KK systems by means of the x 2 test. The probabilities that the observed distributions originate from their corresponding phase-space distributions are <0.0001 for the E^ system and <0. 01 for the KK system. The large x 2 values arise mainly from the single peaks appearing in each curve.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
1

Year Published

1963
1963
1968
1968

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(6 citation statements)
references
References 6 publications
0
5
1
Order By: Relevance
“…The present p +p scattering results do show a shrinkage of this type consistent with the Regge pole prediction but the 7r" +p scattering shows no shrinkage, thus contradicting the assumption of dominance of the strong interactions by a single vacuum pole. Our results are also inconsistent with the predictions of the three-pole model of Hadjioannou et al 4 and Drell, 5 which was developed to explain the total cross-section data-which are inconsistent with single-pole prediction. In the three-pole model F in Eq.…”
contrasting
confidence: 99%
See 1 more Smart Citation
“…The present p +p scattering results do show a shrinkage of this type consistent with the Regge pole prediction but the 7r" +p scattering shows no shrinkage, thus contradicting the assumption of dominance of the strong interactions by a single vacuum pole. Our results are also inconsistent with the predictions of the three-pole model of Hadjioannou et al 4 and Drell, 5 which was developed to explain the total cross-section data-which are inconsistent with single-pole prediction. In the three-pole model F in Eq.…”
contrasting
confidence: 99%
“…The vacuum pole analysis certainly fits and so would a simple three-pole analysis following the method of Hadjioannou et al 4 The fact that the slope is smaller than the original value proposed 1 is not significant, since this was merely a reasonable value. In a previous p+p (12-26 BeV/c, £ = 0-1) experiment and analysis, there is a log-log plot equivalent to our Fig.…”
Section: Giving Log [F/^t] =Logf+[2^a) -2]log(s/so) O' (2)mentioning
confidence: 85%
“…The only strong evidence for a zero exists not for P, which is under consideration here, but for the oo pole. 10 Experimentally it is observed that at a given energy, dcr/dt for "pp at t= 0 is much larger than that for pp and falls off very rapidly as -2 increases. 11,12 In fact, it goes below the pp value at around -£-0.15.…”
Section: Ackn O Wledgmentsmentioning
confidence: 95%
“…i?i(0 = «r[(/-4m ir a )/(/+c)]>o, ^4w" 2 , e^ 1, (10) where X 0 =a(4w 2 7r )+i and c is a positive constant. There is an additional logarithmic factor in (10) which has a negative sign near threshold but becomes positive eventually.…”
Section: Ackn O Wledgmentsmentioning
confidence: 99%
“…We have found the form of <}>i(s) appropriate to the Pomeranchuk trajectory which controls the diffraction peak, but the chief force in TT-TT scattering is the p trajectory exchange, and we need to know the behavior of its residue. Unfortunately, its contribution to N-N scattering, where it will account for the differences between p-p and n-p, is very small, 30 and so has not been determined. For TT-N scattering the p trajectory is important in the charge exchange process T~p->ir°n.…”
Section: The T Experimental Situationmentioning
confidence: 99%